The The Latest Trend in Utilization of Organic Fertilizer for Improving Group Productivity Farming - Maidawati; Rina Sepriani; Ihsanul Fuadi (Jurnal Teknologi, 2022)
The Pejuang Muda or Young Fighters Program was a new program initiated by the Ministry of Social Affairs in 2021 in collaboration with the Free Learning Program of the Ministry of Education, Culture, Research, and Technology, as well as the Ministry of Religion. This program, involving active students as participants from various universities, aims to help update the Social Welfare Integrated Data (SWID), in addition to mapping and designing social programs based on social empowerment in all provinces in Indonesia. Starting from the eight forms of learning activities accommodated by the Merdeka Campus Program, Pejuang Muda Program took the form of learning activities. The focus of the program was the formation of social and economic growth in various locations in Indonesia through community empowerment. Such program can be used to solve social problems that were often encounter in Nagari Kinari were cow dung not processed or utilized properly by local farmers. Such as finding cow dung scattered on roads, residential areas, which resulted in environmental pollution and improves soil physical, chemical, and biological properties. The purpose of this study was to focus on the use of organic fertilizers with the aim of increasing production of environmentally friendly and cost-effective agricultural products aided by the Pejuang Muda Program. This type of research is qualitative descriptive in nature and the researcher also involves the community in Nagari Kinari to obtain data through observation and interviews. In carrying out this research, farmer groups in Nagari Kinari and the people of Nagari Kinari gain insight into new knowledge and understanding about the processing and benefits of organic fertilizers directly and through the practice carried out during training, the community was able to apply it directly in the field. Hence it aided to solve social and economic problems simultaneously.